Diagnóstico de las estrategias de marketing aplicadas dentro de empresas hoteleras de la ciudad de Ibarra – mbabura. - Moreno Martinez, Erika Daniela (2024)
The research focuses on diagnosing the marketing strategies used in hotel companies in the city of Ibarra, Imbabura, considering the importance of the tourism and hotel sector for the local economy. The objective is to understand the current state of marketing strategies in hotels located in the urban area of the city of Ibarra The methodology combines qualitative approaches, through interviews with experts, and quantitative approaches, through surveys of hotels. Previous research related to marketing strategies, digital media, customer attraction, and market share will also be analyzed. The present work reflects a wide range of hotel offerings in Ibarra, but with limited and outdated marketing strategies, mainly relying on word-of-mouth marketing. The need to conduct market studies, train staff, establish alliances, optimize digital marketing, implement segmented advertising campaigns, and promote the city's tourist attractions is highlighted.